Faculty Profile Management System Using IRINS for the Analysis of Research Performance in the Field of Science and Technology - S. Thanuskodi; P. Kannan (International Journal of Information Science and Management)
Academic institutes and Research and Development organizations collect, curate, and organize research-related activities from various sources. The Faculty Profile System or Research Information Management System plays a crucial role in academic institutions organizing scholarly communication data. The research-related metadata collected through the Faculty Profile System could be used for various purposes, including research assessment of faculty and department, decision-making on allocating funding, and ranking of the institute. The study aims to develop a faculty profile management system using the Indian Research Information Network System (IRINS) for seven Indian Institute of Technology (IIT) and analyze the faculty members' research contributions through bibliometric indicators. The study attempted to analyze seven IITs' research performance based on the publications and citations from 2010-2019.   This study emphasized evaluating the faculty and organization's research performance through quantity, impact, quality, and importance. Quantity refers to the number of publications; quality refers to the number of papers published in a highly impacted journal; impact refers to measuring the researcher's influence and evaluation by the number of citations received by the faculty or organization. This paper examines the analysis of research performance in the field of Science and Technology.